Penyesuaian Politik Luar Negeri Indonesia terhadap Dinamika Dunia Internasional di Awal Abad 21: Penggunaan Identitas Islam Moderat - Manggala, Pandu Utama (Global: Jurnal Politik Internasional, 2007)
This article tries to analyze Indonesia's foreign policy at the early 2Ist century, especially during the period of post 9/11 terrorist attack. Since then, the international dynamics focuses more on countries in which Moslem society become the majority, mostly caused by the spread of inter-subjective discourse on the idea of war against terrorism promoted by the government of the United States of America. America then pays more attention on those countries, because they are suspected to be the 'source' of contemporary terrorist movements. Indonesia then, as an Islamic-majority country tries to build bridge between the western countries and Islamic countries. The Indonesian government attempt to construct the image that Islam can also stand in line with democracy. For that reason, Department of Foreign Affairs of the Republic of Indonesia (DEPLU RI) builds the identity of Indonesian foreign policy as a 'Moderate-Islamic country'. However, on the reality, Indonesian foreign policy's new identity hasn't worked well, because Islam in Indonesia never comes up as the mainstream of Indonesian politics. By using the constructivi s t approach, thi s article tries to explain why the moderate-Islamic identity of Indonesian foreign policy failed to raise Indonesia image in the international world